Social, environmental, socio-environmental and environment vulnerability: Concepts and conceptions - Gonçalves, Elton de Oliveira; Grigio, Alfredo Marcelo; Souza Neto, Luiz Tavernard de; Diodato, Marco Antonio (Revista Nacional de Gerenciamento de Cidades, 2022)
The growing demand for the operationalization of scientific concepts makes them to be proposed as an intervention design. In this context, the objective of this study is to know the concepts and conceptions that identify vulnerability, be it social, environmental or socio-environmental, as well as to distinguish the types of vulnerability; identify social, environmental and socio-environmental vulnerability factors; and, analyze the role of public policies in mitigating vulnerabilities. Therefore, a bibliographic research was carried out with a descriptive approach. It was found that people in general need to be aware of the risks and vulnerabilities that are permanently observed in cities. The rapid and intense alteration of natural landscapes into artificial landscapes generated, above all, by human constructions, and which characterize urban spaces, results in numerous problems for cities, requiring public policies to create defense mechanisms for risk factors. so that all together can overcome vulnerabilities, be they social, environmental or socio-environmental.